2010
DOI: 10.3109/07357907.2010.512597
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of GPR56, Transglutaminase 2, and NF-κB in Esophageal Squamous Cell Carcinoma

Abstract: Proteins do not operate as individual units, and components of intracellular canonical pathways often cross talk in tumor genesis. We hypothesized that G-protein-coupled receptor 56 (GPR56), transglutaminase (TG2), and nuclear factor-κB (NF-κB) may collaborate in interconnected pathways and contribute to the aggressive behavior of esophageal squamous cell carcinoma (ESCC). Immunohistochemical analysis of GPR56, TG2, and NF-κB was carried out using ESCC tissue microarrays. Immunostaining of all the three protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Biological and clinical lines of evidence have established that NF-κB is constitutively activated in ESCC (39,40). Interestingly, we found that high levels of NF-κB are recruited to the promoter region of AGK, according to ChIP sequencing tracks in the UCSC genome browser (http://genome.ucsc.edu/cgi-bin/hgGateway).…”
Section: Discussionmentioning
confidence: 91%
“…Biological and clinical lines of evidence have established that NF-κB is constitutively activated in ESCC (39,40). Interestingly, we found that high levels of NF-κB are recruited to the promoter region of AGK, according to ChIP sequencing tracks in the UCSC genome browser (http://genome.ucsc.edu/cgi-bin/hgGateway).…”
Section: Discussionmentioning
confidence: 91%
“…On one hand, expression levels of ADGRG1 (GPR56) were found to be inversely correlated with the metastatic potential of melanoma cell lines (Zendman et al, 1999;Xu et al, 2006), and reexpression of the receptor led to a reduction in melanoma growth and metastasis . On the other hand, ADGRG1 (GPR56) was found to be upregulated in various cancer types (Shashidhar et al, 2005;Kausar et al, 2011) and in tumor cell lines (Ke et al, 2007), compared with normal samples.…”
Section: Skeletal Muscle and Bonementioning
confidence: 99%
“…Numerous studies have revealed that constitutive activation of NF-kB signaling plays vital roles in the development and progression of ESCCs, and blockade of the NF-kB pathway can inhibit ESCC proliferation, sensitize ESCCs to chemotherapeutic drugs and suppress angiogenesis and metastasis in ESCCs (3,4). However, the precise molecular mechanisms which regulate the NF-kB pathway in ESCCs are still not completely understood.…”
Section: Introductionmentioning
confidence: 99%